INSERTION METHOD USING MUSIC NOTES - M. YAMUNA; SANKAR, A.; SIDDARTH RAVICHANDRAN; V. HARISH (Innovare Journal of Engineering and Technology, 2014)
Communication signals are openly available as they are propagated. Secured transmission is always a question and various methods are devised. Â Use of music notes is not in wide use in encryption of data. Any musical note consists of seven basic keys. In this paper we propose an insertion method with the seven music keys are used as a tool of encryption.